If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2w + -6) + 4(-1 + -5w) = o Reorder the terms: 8(-6 + 2w) + 4(-1 + -5w) = o (-6 * 8 + 2w * 8) + 4(-1 + -5w) = o (-48 + 16w) + 4(-1 + -5w) = o -48 + 16w + (-1 * 4 + -5w * 4) = o -48 + 16w + (-4 + -20w) = o Reorder the terms: -48 + -4 + 16w + -20w = o Combine like terms: -48 + -4 = -52 -52 + 16w + -20w = o Combine like terms: 16w + -20w = -4w -52 + -4w = o Solving -52 + -4w = o Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '52' to each side of the equation. -52 + 52 + -4w = 52 + o Combine like terms: -52 + 52 = 0 0 + -4w = 52 + o -4w = 52 + o Divide each side by '-4'. w = -13 + -0.25o Simplifying w = -13 + -0.25o
| (5y-3)(y+2)=0 | | 2.3=1.7+m | | 25=x^2+36 | | y-5=4 | | 2x-14=3(x+3)(x+3)-8x^2 | | y=6x+2 | | -6(x-2)+4(3-6x)=36 | | y^2-6+3y=4(y-5)(y-5)-12 | | (7y-1)(2y-3)=0 | | y^2=21 | | 3x+35=7(x+5)-4x | | -75+10x=105 | | 2x^2=228 | | -75+10x=05 | | .5(y+4)(y+4)-6(y+3)=7 | | 3(x-2)=9x-9-6x | | 3(x-2)=6x-4-3x | | 0=4x^2+19x-54 | | 3x-9=2x-4(x-1) | | m^2=48 | | 3x^2-6x+5=-2(x+1)-10 | | h^2+4=40 | | 3x+5=10x+26 | | 12u^2+30u=0 | | x^2+(x-3)(x+3)=65 | | h^2=36 | | =5x^2+19x-54 | | -29.5+0.1p=0.9p+5.3 | | m^2-11m-12=0 | | 2-(4x+7)=3+2(x+2) | | x+2=8x | | h^4=40 |